Analysis of Factors of Sustainable Financial Consumerism Among Indonesian University Students - Subroto Rapih; Yosep Tegar Prameswara; Hani Febriyanti; Arvano Sahwa Riordan; Az-Zahra Ayu Permata (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
This study examines how financial capability and digital influence shape sustainable financial consumerism among Indonesian university students, with financial decision-making as a mediating factor. Using data from 432 undergraduate students at ten universities in Central Java and analyzed through PLS-SEM, the results show that both financial capability and exposure to influencers positively influence financial decision-making and sustainable financial behavior. Financial decision-making significantly mediates this relationship, highlighting informed judgment as a key mechanism linking knowledge and social influence to responsible finance. Theoretically, this study integrates financial capability and digital influence within the framework of sustainability in a developing economy. Practically, it emphasizes the need to strengthen decision-making competencies in financial education, implement ethical standards for influencers, and promote sustainable financial access to foster a financially capable and sustainability-oriented younger generation.